2004
DOI: 10.1021/jm0309607
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Ligand Binding Affinity and Orientation of Xenoestrogens to the Estrogen Receptor by Molecular Dynamics Simulations and the Linear Interaction Energy Method

Abstract: Exposure to environmental estrogens has been proposed as a risk factor for disruption of reproductive development and tumorigenesis of humans and wildlife (McLachlan, J. A.; Korach, K. S.; Newbold, R. R.; Degen, G. H. Diethylstilbestrol and other estrogens in the environment. Fundam. Appl. Toxicol. 1984, 4, 686-691). In recent years, many structurally diverse environmental compounds have been identified as estrogens. A reliable computational method for determining estrogen receptor (ER) binding affinity is of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 50 publications
4
93
0
Order By: Relevance
“…An increasing number of structurally diverse estrogenic compounds have been identified and proposed as risk factors for disruption of reproductive development and tumorigenesis (23). Estrogenic chemicals are defined as substances, interacting and activating ER, which may interfere with the endocrine system (24).…”
mentioning
confidence: 99%
“…An increasing number of structurally diverse estrogenic compounds have been identified and proposed as risk factors for disruption of reproductive development and tumorigenesis (23). Estrogenic chemicals are defined as substances, interacting and activating ER, which may interfere with the endocrine system (24).…”
mentioning
confidence: 99%
“…The system of choice is the ligand-binding domain (LBD) of the estrogen receptor (ER). Previous computational approaches to computing binding free energies for this system involve empirical regression-based methods (12)(13)(14), docking efforts (15), and free-energy calculations from molecular dynamics simulations (3,6,16). A great number of structurally diverse compounds have been shown to interact with the ER LBD (14,(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…3, ESA01-ESA10) used in this study was identical to that reported earlier. 27 In total, the database used for screening ligands against the ER-antagonist complex [Protein Data Bank (PDB) code: 3ert 26 ] and ER-agonist complex (PDB code: 1gwr 28 ) contained 1000 molecules; that is, 990 random compounds were the same for the 2 screens. In addition, 3 ER-antagonist complexes (PDB codes: 1err, 3ert, and 1hj1) and 4 ER-agonist complexes (PDB codes: 1gwr, 1l2i, 1qkm, and 3erd) with experimentally determined X-ray structures from the PDB were selected to evaluate not only the docking accuracy but also the pharmacological consensuses evolved from known active ligands (i.e., Figs.…”
Section: Preparations Of Ligand Databases and Target Proteinsmentioning
confidence: 99%